Perputaran Total Aset Dan Perputaran Piutang Berpengaruh Terhadap Return on Asset - Karmila Karmila; Herman Sjahruddin; Jannati Tangngisalu; Kristina Parinsi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to examine the impact of total asset turnover and receivables turnover on the return on equity of retail companies listed on the Indonesian Stock Exchange. The data collection is based on secondary data from companies' annual financial reports, which can be accessed through the website www.idx.co.id. The population in this study were retail trade sector manufacturing companies listed on the Indonesia Stock Exchange during 2020-2022, of which there were 25 companies, while the sample taken was 20 companies with sampling techniques using purposive sampling. The data processed were 60 samples that had been tested for classical assumptions in the form of testing the assumptions of normality, multicollinearity, heterocedacity and autocorrelation. The data analysis method uses panel data regression techniques. The results showed that total asset turnover had a positive and significant effect on ROA and receivable turnover had a positive and insignificant effect on ROA.